A Bibliometric Analysis of Employee Performance in the Context of Cognitive Dissonance Using Visualizing Networks - Sachdeva, Channi; Gangwar, Veer P. (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: This study was designed to give a comprehensively updated bibliometric summary of employee performance when faced with cognitive dissonance in light of recent imperatives and expanding scholarly interest. OBJECTIVE: This research provided a deep knowledge of references, cited sources, countries through network map, relevant sources map with table, relevant authors map with table, frequent keywords used by authors network map, citations per year graph, and co-occurrence of network with networking map. METHOD: In the study, the Scopus database was used to analyse large data. Biblioshiny software was also used for the analysis and verified using a VOS viewer. A mixed (combination of several) techniques is the main focus of the methodological procedure. 400 Scopus-indexed articles and 5 conference papers have been taken to prepare this bibliometrics review with the help of biblioshiny and Vos viewer software. RESULT: The results reveal that employee performance depends on their beliefs and attitudes. These two factors fall under cognitive dissonance theory (CDT). CONCLUSION: It is also fruitful for organizations to study CDT theory for organizational development and employee performance growth.